Publication of clinical trials performed in Peru - Heredia, Paula (2018)
2797/5000 Mr. Editor Clinical trials are characterized by having one of the highest levels of scientific evidence1. A properly designed, executed and reported clinical trial constitutes the gold standard in the evaluation of medical interventions. Therefore, timely dissemination is essential to ensure that the clinical decisions made by physicians and patients reflect the best available evidence2. However, the literature reports that in the last decade only half of clinical trials carried out worldwide have been published3. A study conducted in the United States described that less than 30% of clinical trials were published within 2 years of completion in that country4. In the case of Latin America, only 15% of published clinical trials are reported5. In Peru, information regarding clinical trials conducted in the country is available in an updated virtual platform: Peruvian Registry of Clinical Trials (REPEC). A study that analyzed this platform reported that during 1995-2012 there were a total of 1475 clinical trial protocols, of which 85% were authorized and of these 62% were completed6. The statistics in our country in the year 2005, stated that the number of clinical trials authorized by the Ministry of Health from 1995 to the first quarter of 2003 was 323, highlighting a sustained annual increase in the number of studies approved1 in 1995 to83 in 20027. A study in 2012 reports the number of publications of Peruvian autochthonous clinical trials from 1995 to 2011, which remains constant, showing that the increase in the execution of multinational clinical trials is not related to the execution of clinical trials. native8 On the other hand, despite the fact that there is a virtual platform for the registration of all clinical trials conducted in our country, there is no information about the publication of all of these in biomedical journals. The importance of this is the participation of a Peruvian population in autochthonous or multinational clinical trials, so that their results may be more applicable to patients in the country. However, if these are not published, they will never be used by health professionals. That is why we are currently carrying out a study that delves into the reality of clinical trials in our country beyond just registration. The importance of these results would serve to propose new regulations when registering a clinical trial project in the REPEC. In addition, a model for updating the data collection form may be proposed, including the results and publication of the clinical trial. DOI: 10.25176/RFMH.v18.n3.1602